TAX AUDIT AND TAXPAYER COMPLIANCE - Judijanto, Loso; S Pentanurbowo; Erwin; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Tax audits alone may not be effective enough in encouraging tax compliance without being supported by thorough tax education and the use of technology in the tax system. The research method used is the literature research method. The results show that tax audit has a deterrent effect on tax avoidance, but its effectiveness increases significantly when accompanied by tax education that provides knowledge and forms a positive attitude towards taxes. In addition, the integration of technology in the tax administration process makes it easier for taxpayers to fulfill their obligations, improving tax compliance through increased efficiency and transparency. Thus, success in improving tax compliance requires a combination of fair and consistent enforcement of regulations, informative and awareness-building education initiatives, and the development of a supportive technological infrastructure. The implications of these findings provide guidance for tax policy makers to design more effective strategies to improve tax compliance in the future.